KAREL GADÁNYI – DOBITNIK MEDALJE ZA ZASLUGE - Jesenšek, Marko (Slavia Centralis, 2020)
The article presents the life and scientific research work of Karel Gadányi, the receiver of the Medal of Merit for the successful placement of Slovene studies in the Hungarian higher education area and the support of Slovenes in Hungary in preserving their mother tongue and culture.
Keywords: Karel Gadányi; Slovenian studies; Hungarian Slovenians; Hungary; report